A new Orthogonal - Diamond Search algorithm for Motion Estimation - Hamid, N. A.; Darsono, A. M.; Manap, N. A.; Manap, R. A.; Sulaiman, H. A. (2014 International Conference on Computer, Communications, and Control Technology (I4CT), 2014)
Many fast Block Matching Algorithm or BMA have been proposed and developed in recent years in order to reduce the computational cost while maintaining the quality of the video signal. In this paper, a new Orthogonal-Diamond Search (ODS) is proposed which employs an orthogonal-shaped search pattern in the first step and then is switched into small diamond-shaped search pattern for the next step. The proposed algorithm and several established algorithms, namely Full Search (FS), Three-Step Search (TSS) and Diamond Search (DS) are implemented using MATLAB and their performance are being compared and analyzed in terms of computational complexity, peak signal-to-noise ratio (PSNR), and number of search points. Simulation result shows that the proposed algorithm can find motion vector with fewer number of search points while maintains close performance of video quality with other selected algorithms.